2019
DOI: 10.1016/j.joca.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, humanistic, and economic burden of osteoarthritis among noninstitutionalized adults in the United States

Abstract: Objective: To estimate the burden of osteoarthritis (OA) among noninstitutionalized adults (!18 years of age) in the US. Design: Weighted nationally representative data from the 2015 Medical Expenditure Panel Survey were used to estimate OA prevalence in noninstitutionalized adults and compare adults with OA to those without OA for clinical (pain interference with activities [PIA], functional limitations), humanistic (health-related quality-of-life [HRQoL]) and economic outcomes (healthcare costs, wage loss). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
113
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 22 publications
8
113
0
2
Order By: Relevance
“…Consistent with other recent studies that have addressed the relationship of current OA severity and HCRU crosssectionally (in the months pre-severity assessment) [8] and longitudinally (in the months post-severity assessment) [12], both methods identified increased hospitalizations and OArelated HCP visits as positively associated with pain severity. Although hospitalizations for OA are infrequent, they represent a large proportion of the overall economic cost of OA management [18].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with other recent studies that have addressed the relationship of current OA severity and HCRU crosssectionally (in the months pre-severity assessment) [8] and longitudinally (in the months post-severity assessment) [12], both methods identified increased hospitalizations and OArelated HCP visits as positively associated with pain severity. Although hospitalizations for OA are infrequent, they represent a large proportion of the overall economic cost of OA management [18].…”
Section: Discussionsupporting
confidence: 87%
“…A potential consequence of a rise in OA rates is an increasing burden on healthcare resources [6]. Recent studies have shown that in the US, patients with OA utilized more healthcare resources compared to similar patients without OA in privately insured and a noninstitutionalized, nationally represented study sample [7,8]. This equated to increases in healthcare costs that were 4 times and 2.5 times higher in patients with OA versus without in the respective populations [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total joint replacement (TJR) continues to be one of the most successful surgical interventions as evidenced by consistent pain relief and restoration of physical function and quality of life in patients with advanced osteoarthritis (OA) 1 . The lifetime risk of undergoing TJR surgery for the 13% of adults (approximately 31 million population) in the United States (US) diagnosed with OA of the hip and knee is steadily increasing alongside total episode costs associated with these procedures (estimated at $45 billion per annum) 2–4 . Based on current trends, procedural volumes and levels of spending seem only set to escalate for the 78 million American adults (26%) projected to experience hip and knee OA by 2040 5–8 …”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 In addition, the economic burden of OA is shown by high healthcare costs and high indirect costs. 5 …”
Section: Introductionmentioning
confidence: 99%